2008
DOI: 10.1177/000312240807300201
|View full text |Cite
|
Sign up to set email alerts
|

The Social Connectedness of Older Adults: A National Profile

Abstract: For decades, scholars have wrestled with the notion that old age is characterized by social isolation. However, there has been no systematic, nationally representative evaluation of this possibility in terms of social network connectedness. In this paper, the authors develop a profile of older adults' social integration with respect to nine dimensions of connectedness to interpersonal networks and voluntary associations. The authors use new data from the National Social Life, Health, and Aging Project (NSHAP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
632
8
46

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 761 publications
(720 citation statements)
references
References 78 publications
34
632
8
46
Order By: Relevance
“…Given the documented health and wellbeing benefits of high social engagement at older ages (Berkman et al 2004;Pillemer et al 2000), decreased engagement among less-advantaged retirees may either widen or explain observed health disparities at older ages. Our findings are generally consistent with previous research suggesting that membership in certain types of organizations tends to be higher after retirement (Cornwell et al 2008), particularly religious attendance and volunteerism (Miller and Nakamura 1996), although there is some evidence that trends in religious attendance may not continue for future retirement cohorts (Broese Van Groenou and Deeg 2010). Time since retirement as a determinant of engagement changes?…”
Section: Organizational Activity Participationsupporting
confidence: 91%
See 1 more Smart Citation
“…Given the documented health and wellbeing benefits of high social engagement at older ages (Berkman et al 2004;Pillemer et al 2000), decreased engagement among less-advantaged retirees may either widen or explain observed health disparities at older ages. Our findings are generally consistent with previous research suggesting that membership in certain types of organizations tends to be higher after retirement (Cornwell et al 2008), particularly religious attendance and volunteerism (Miller and Nakamura 1996), although there is some evidence that trends in religious attendance may not continue for future retirement cohorts (Broese Van Groenou and Deeg 2010). Time since retirement as a determinant of engagement changes?…”
Section: Organizational Activity Participationsupporting
confidence: 91%
“…These overall findings of increased engagement during retirement suggest that retirement could have provided participants with more time to spend with their families and friends. Some prior research finds that social networks tend to contract as individuals age (Cornwell et al 2008;Schnittker 2007), while others have found no change (Pillemer and Glasgow 2001). However, our findings suggest that networks grew after retirement, rather than contracted.…”
Section: Social Ties With Family and Friendsmentioning
confidence: 99%
“…Importantly, this is distinct from most older adults who have increased levels of community engagement with age. 53 This was true even for individuals screening positive for MCI, suggesting an early indicator of cognitive loss. We also hypothesized that lower cognition would be associated with social isolation from family and friends, which was not the case.…”
Section: Discussionmentioning
confidence: 95%
“…In general, the size of the social network decreases with age (Cornwell et al, 2008(Cornwell et al, , 2009). Family plays a central role in the social relations of the elderly.…”
Section: Brand Relationsmentioning
confidence: 99%